Investigating strategies used to integrate Technology (the computer and related devices) into Remedial Education - LASHLEY, LIDON. C.; Elliott, Volda (Social Science Learning Education Journal, 2017)
This study was undertaken to investigate the use of technology in remedial education within Guyanaâs mainstream primary schools and the strategies used to integrate technology in remedial education. This research identified possible solutions to reverse the negative views towards the use of technology in remedial education within Guyanaâs mainstream primary schools specifically region # 5.Â  Two classes were used as experimental group and the other two as control group. The Quasi Experimental, Non Equivalent Control Group design was employed for this study. The instrument which was used for data collection was a teacher made test. The reliability coefficient of the instrument was 0.553 significant at alpha 0.01. The data were analyzed using mean and inferential statistics - t-test, and ANOVA.It was concluded that integrating technology in remedial education within Guyanaâs mainstream primary schools can significantly improve learnersâ academic performance and the rate at which concepts are grasped at the primary level.Further, the results of this study show that learners who are allowed to use the products of technology in there learning interactions in remedial classes demonstrated a better attitude and willingness towards their academic work. The outcome of the study show that the academic performance of learners who were given instructions and support using the products of technology significantly improved their performance in a shorter period that their peers who were exposed to traditional methods of instructions.